2017
DOI: 10.1002/aic.15876
|View full text |Cite
|
Sign up to set email alerts
|

A rigorous method to evaluate the consistency of experimental data in phase equilibria. Application to VLE and VLLE

Abstract: This work forms part of a broader study that describes a methodology to validate experimental data of phase equilibria for multicomponent systems from a thermodynamic‐mathematical perspective. The goal of this article is to present and justify this method and to study its application to vapor–liquid equilibria (VLE) and vapor–liquid–liquid equilibria (VLLE), obtained under isobaric/isothermal conditions. A procedure based on the Gibbs‐Duhem equation is established which presents two independent calculation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 209 publications
1
46
0
Order By: Relevance
“…The problem lies in confirming whether the experimental information obtained is coherent/consistent with the theoretical formalism established by thermodynamics . As explained in previous articles, phase equilibria experimentation usually leads to measuring a number of variables larger than those established by the degrees of freedom of the system studied; clearly oversized as determined by the phase rule. Therefore, a mathematical‐thermodynamic tool must be found that checks the degree of correlation between the variables found experimentally and scientific formalism.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…The problem lies in confirming whether the experimental information obtained is coherent/consistent with the theoretical formalism established by thermodynamics . As explained in previous articles, phase equilibria experimentation usually leads to measuring a number of variables larger than those established by the degrees of freedom of the system studied; clearly oversized as determined by the phase rule. Therefore, a mathematical‐thermodynamic tool must be found that checks the degree of correlation between the variables found experimentally and scientific formalism.…”
Section: Introductionmentioning
confidence: 89%
“…To carry out some applications that show the practical utility of the previous mathematical formalism, binary solutions are chosen (with a volatile and a nonvolatile component), as the extension to multicomponent solutions is immediate as described previously . Likewise, the application to VLLE is similar to the cases already presented . The particularization of Equation for binary solutions produces: []xnvlnγnvx1p,T1=φψ()italicdψdx1 …”
Section: Thermodynamics Of the Consistency Test For Vapor–liquid Equimentioning
confidence: 99%
See 3 more Smart Citations